Histopathological Features of Primary Cutaneous Diffuse Large B-Cell Lymphoma Leg Type: A Case Report - Triasari Oktavriana; Ayu Kusuma Dewi; Ambar Mudigdo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL-LT), is a rare and aggressive lymphoma with poor prognostic. It is difficult to diagnose PCDLBCL-LT at an early stage due to its nonspecific manifestations that overlap with other lymphomas. A histopathological examination can be performed to establish the diagnosis. Case Presentation: A 74-year-old female presented with itchy red, swollen patches accompanied by a burning sensation on both her legs. Clinical examination revealed a hard ping pong ball-sized lump palpable on her left inner thigh. Haematoxylin eosin staining demonstrated the proliferation of diffused neoplastic cells, homogenous cells with atypical nuclei, and mitoses. Immunohistochemical examination revealed positive for CD 45 as well as CD 20 and negative for CD3. These findings were consistent with a diagnosis of PCDLBCL-LT. Conclusion: The presented case demonstrates that skin lesions in patients with diagnosed PCDLBCL-LT may have a variable clinical presentation. Histologically is characterized by a diffuse dermal infiltrate mostly consisting of activated B-cell (centroblast) and activated lymphocyte (immunoblast), with high mitotic activity and a minimal T-reactive component. Immunohistochemical analysis is necessary for establishing the diagnosis of PCDLBCL-LT which shows positive markers for CD 45, CD 20, CD79a, Bcl-2, MUM-1, FOX-P1, CD10, IgM, CD 138, Ki-67, CD 30 and MYC.